Bioactive Peptides from Velvet Bean Tempe: Neutrase-Catalyzed Production in Membrane Reactor - Azis Boing Sitanggang; Tsaniyah Ayu Mauliasyam; Nadine Kurniadi; Slamet Budijanto; Ho-Shing Wu (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2023)
Velvet beans are potential sources of parent proteins for bioactive peptide production. In this study, a combination of fermentation and neutrase-catalyzed continuous hydrolysis in an enzymatic membrane reactor was performed to produce antioxidative and angiotensin I-converting enzyme inhibitory (ACEi) peptides. The optimum operating conditions were τ = 6 h and [E]/[S] = 7.5%. The resulting permeate, which was a<10-kDa fraction, exhibited antioxidant activity at 0.38 mg ascorbic acid equivalent antioxidant capacity (AEAC)/mL (2,2-diphenyl-1-picrylhydrazyl, DPPH inhibition) and 0.26 mg AEAC/mL (ferric reducing antioxidant power, FRAP), and ACEi activity of 81.02%. Further fractionation of the permeate increased the ACEi activity in which 2-kDa fraction showed the most potent activity (IC50 = 0.23 µg protein/mL). The IC50 value of the outcome was comparable to those reported in the literature for velvet bean-based peptides. Furthermore, this study suggests that neutrase is a good catalyst candidate for the synthesis of bioactive peptides from velvet beans.